The latest therapeutic reports on short-term and long-term prophylaxis in the treatment of hereditary angioedema - Kozłowski, Maciej; Żurawska, Karolina; Poziomkowska-Gęsicka, Iwona (Alergologia Polska - Polish Journal of Allergology, 2024)
Hereditary angioedema (HAE) is a rare but serious condition that manifests itself as self-limiting swelling of the subcutaneous and submucosal tissue. Symptoms can occur on various parts of the body, including the gastrointestinal tract, face and extremities, with the most dangerous form being swelling of the larynx and airways, which can be life threatening for the patient. Triggers can be trauma, surgical procedures, excessive stress or exposure to estrogen. The diagnosis of HAE is based on a thorough medical history, analysis of the family history, specialized laboratory tests and genetic analysis. Various medications are used in the treatment and prevention of HAE, both for short- and long-term prevention. Patients with HAE must be aware of the need to receive medication promptly in the event of an attack, as well as the importance of regular prophylactic therapy, which can significantly reduce the frequency and severity of attacks, allowing them to lead normal lives. Modern research and development of therapy help to improve the quality of life of patients with HAE, giving them better control of the disease.